Amplification of Inflammation by Lubricin Deficiency Implicated in Incident, Erosive Gout Independent of Hyperuricemia. Issue 5 (10th March 2023) - Elsaid, Khaled; Merriman, Tony R.; Rossitto, Leigh‐Ana; Liu‐Bryan, Ru; Karsh, Jacob; Phipps‐Green, Amanda; Jay, Gregory D.; Elsayed, Sandy; Qadri, Marwa; Miner, Marin; Cadzow, Murray; Dambruoso, Talia J.; et al.
Abstract : Objective: In gout, hyperuricemia promotes urate crystal deposition, which stimulates the NLRP3 inflammasome and interleukin‐1β (IL‐1β)–mediated arthritis. Incident gout without background hyperuricemia is rarely reported. To identify hyperuricemia‐independent mechanisms driving gout incidence and progression, we characterized erosive urate crystalline inflammatory arthritis in a young female patient with normouricemia diagnosed as having sufficient and weighted classification criteria for gout according to the American College of Rheumatology (ACR)/EULAR gout classification criteria (the proband). Methods: We conducted whole‐genome sequencing, quantitative proteomics, whole‐blood RNA‐sequencing analysis using serum samples from the proband. We used a mouse model of IL‐1β–induced knee synovitis to characterize proband candidate genes, biomarkers, and pathogenic mechanisms of gout. Results: Lubricin level was attenuated in human proband serum and associated with elevated acute‐phase reactants and inflammatory whole‐blood transcripts and transcriptional pathways. The proband had predicted damaging gene variants of NLRP3 and of inter‐α trypsin inhibitor heavy chain 3, an inhibitor of lubricin‐degrading cathepsin G. Changes in the proband's serum protein interactome network supported enhanced lubricin degradation, with cathepsin G activity increased relative to its inhibitors, SERPINB6 and thrombospondin 1. Activation of Toll‐like receptor 2 (TLR‐2) suppressed levels of lubricin mRNA and lubricin release in cultured human synovial fibroblasts ( P  < 0.01). Lubricin blunted urate crystal precipitation and IL‐1β induction of xanthine oxidase and urate in cultured macrophages ( P  < 0.001). In lubricin‐deficient mice, injection of IL‐1β in knees increased xanthine oxidase–positive synovial resident M1 macrophages ( P  < 0.05). Conclusion: Our findings linked normouricemic erosive gout to attenuated lubricin, with impaired control of cathepsin G activity, compounded by deleterious NLRP3 variants. Lubricin suppressed monosodium urate crystallization and blunted IL‐1β–induced increases in xanthine oxidase and urate in macrophages. The collective activities of articular lubricin that could limit incident and erosive gouty arthritis independently of hyperuricemia are subject to disruption by inflammation, activated cathepsin G, and synovial fibroblast TLR‐2 signaling. Abstract :